Expression 19: "x" equals negative 2 left brace, negative 4.9 5 5 less than or equal to "y" less than or equal to 4.9 5 5 , right bracex=−2−4.955≤y≤4.955
19
Expression 20: "x" equals 0 left brace, negative 5 less than or equal to "y" less than or equal to 5 , right bracex=0−5≤y≤5
20
Expression 21: "x" equals 2 left brace, negative 4.9 5 5 less than or equal to "y" less than or equal to 4.9 5 5 , right bracex=2−4.955≤y≤4.955
21
Expression 22: "x" equals 4 left brace, negative 4.8 1 9 less than or equal to "y" less than or equal to 4.8 1 9 , right bracex=4−4.819≤y≤4.819
22
Expression 23: "x" equals 6 left brace, negative 4.5 8 3 less than or equal to "y" less than or equal to 4.5 8 3 , right bracex=6−4.583≤y≤4.583
23
Expression 24: "x" equals 8 left brace, negative 4.2 3 less than or equal to "y" less than or equal to 4.2 3 , right bracex=8−4.23≤y≤4.23
24
Expression 25: "x" equals 10 left brace, negative 3.7 2 7 less than or equal to "y" less than or equal to 3.7 2 7 , right bracex=10−3.727≤y≤3.727
25
Expression 26: "x" equals 12 left brace, negative 3 less than or equal to "y" less than or equal to 3 , right bracex=12−3≤y≤3
26
Expression 27: "y" equals negative 1.3 "x" plus 30 left brace, 18 less than or equal to "x" less than or equal to 19.4 1 5 , right bracey=−1.3x+3018≤x≤19.415
27
Expression 28: "y" equals 1.7 "x" minus 30 left brace, 20.4 5 5 less than or equal to "x" less than or equal to 21.6 6 , right bracey=1.7x−3020.455≤x≤21.66
28
Expression 29: left parenthesis, "x" minus 18 , right parenthesis squared plus left parenthesis, "y" minus 7.0 2 , right parenthesis squared equals .2x−182+y−7.022=.2
29
Expression 30: left parenthesis, "x" minus 21.7 , right parenthesis squared plus left parenthesis, "y" minus 7.3 , right parenthesis squared equals .2x−21.72+y−7.32=.2
30
Expression 31: .9sine left parenthesis, 2 "x" plus 2.7 , right parenthesis plus 1.3 left brace, negative 18 greater than or equal to "x" greater than or equal to negative 40 , right brace.9sin2x+2.7+1.3−18≥x≥−40
31
Expression 32: left parenthesis, "x" minus 40 , right parenthesis squared plus left parenthesis, "y" minus 3 , right parenthesis squared equals 12x−402+y−32=12
32
Expression 33: left parenthesis, "x" minus 36 , right parenthesis squared plus left parenthesis, "y" , right parenthesis squared equals 12x−362+y2=12
33
Expression 34: left parenthesis, "x" minus 37 , right parenthesis squared plus left parenthesis, "y" plus 4 , right parenthesis squared equals 12x−372+y+42=12
34
Expression 35: left parenthesis, "x" minus 40 , right parenthesis squared plus left parenthesis, "y" plus 1 , right parenthesis squared equals 2x−402+y+12=2
35
Expression 36: left parenthesis, "x" minus 42 , right parenthesis squared plus left parenthesis, "y" plus 5 , right parenthesis squared equals 12x−422+y+52=12
36
Expression 37: left parenthesis, "x" minus 44 , right parenthesis squared plus left parenthesis, "y" , right parenthesis squared equals 12x−442+y2=12